The Relationship Between Physical Fitness And Shooting Skills Of Perselo Fc Players - Usamah Abadi; Rachmat Hidayat; A. Nurhayati; A. Heri Riswanto (STKIP Muhammadiyah Kuningan, 2023)
Irregular training and lack of time to maintain physical fitness so that it has an impact on the matches that are followed, especially in the finishing, which always fails and causes players to experience significant fatigue. This study aims to determine the physical fitness of the Perselo Fc players' shooting skills. The sample in the survey is 18 Perselo Fc soccer players. The method used in this research is quantitative research with correlational study. The research results on Perselo Fc soccer players showed that Shooting skills are significantly related to physical fitness. The conclusion is that physical fitness greatly affects a person's physique in shooting skills; if you continue to practice repeatedly, it will produce a better shooting technique.